Well drilling composite plugging agent as well as preparation method and use method thereof

By combining modified epoxy resin and curing agent, drilling composite leak plugging agent with high compression and high temperature resistance was prepared, which solved the problems of insufficient compressive resistance and high temperature and easy carbonization of the existing composite leak plugging agent, and achieved a more effective sealing effect.

CN119859514AActive Publication Date: 2025-04-22PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311359757.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The existing composite leak plugging agents take a long time to form high-strength sealing, with a compressive resistance of only 7MPa, and carbonization will occur when the temperature is too high.

Method used

Using a combination of modified epoxy resin, diluent, curing agent and filler, a drilling composite leak plugging agent with excellent compressive resistance and high temperature resistance is prepared by the preparation method of modified epoxy resin and the preparation method of curing agent.

Benefits of technology

The high-strength performance, good high-temperature resistance and appropriate solidification time of composite leak plugging agent are achieved, effectively sealing and improving compressive strength and temperature resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859514A_ABST
    Figure CN119859514A_ABST
Patent Text Reader

Abstract

The invention discloses a drilling composite plugging agent as well as a preparation method and a use method thereof. The drilling composite plugging agent comprises the following components in parts by weight: 30-40 parts of modified epoxy resin, 1-2 parts of a diluent, 4-6 parts of a curing agent and 10-14 parts of filler, the modified epoxy resin is mainly prepared from the following raw materials in parts by weight: 20-30 parts of epoxy resin, 5-6 parts of N-ethyl morpholine and 4-6 parts of polyethylene glycol. The epoxy resin is modified through N-ethyl morpholine and polyethylene glycol, and the epoxy resin provides basic bonding performance; the N-ethyl morpholine can improve the temperature resistance of the epoxy resin; the polyethylene glycol can improve the flexibility of the epoxy resin, so that the compression resistance of the composite plugging agent is enhanced. The modified epoxy resin, the diluent, the curing agent and the filler are matched for use, so that the obtained composite plugging agent has relatively good setting time and high temperature resistance (namely, the plugging agent is not easy to carbonize).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite plugging agents for drilling, and in particular to a composite plugging agent for drilling and a preparation method and a use method thereof. Background Art

[0002] The work of drilling holes in the ground using mechanical equipment or manpower is called drilling. It usually refers to the project of drilling wells and large-diameter water supply wells for the exploration or development of liquid and gaseous minerals such as oil and natural gas. Drilling is widely used in national economic construction.

[0003] Loss is a common problem encountered during the drilling process. In severe cases, it may lead to drill sticking, well collapse, and even the need to fill the well and side-drill, which will bring huge economic losses. Therefore, it is necessary to use plugging agents to seal the leakage.

[0004] The patent application number is CN202010951767.8, which states in the specification that "the high-strength drilling composite plugging agent comprises the following components by mass: 5-25 parts of fiber material, 40-60 parts of rigid material and 15-40 parts of high-strength temperature-resistant material; by mass, the high-strength temperature-resistant material is made of 10 parts of propylene oxide propylene ether, 5 parts of hydroxyethyl acrylate, 30 parts of acrylate glycidol, 15 parts of aminophenol and 40 parts of deionized water. The invention is made by The fiber material, rigid material and high-strength temperature-resistant material are compounded into a new type of drilling composite plugging agent, which has a pressure bearing capacity of more than 7MPa and a temperature resistance of more than 200°C when used, which is significantly improved compared with traditional plugging agents, and the drilling composite plugging agent is applicable to both oil-based drilling fluid and water-based drilling fluid. Although the composite plugging agent provided by the above patent can achieve the plugging effect, it takes a long time to form a high-strength plugging belt, the pressure resistance is only 7MPa, and carbonization will occur when the temperature is too high.

[0005] In summary, the urgent need to develop a composite plugging agent for drilling is a key issue that needs to be solved in the field of plugging material technology. Summary of the invention

[0006] The technical problem to be solved by the present invention is that it takes a long time for the existing composite plugging agent to form a high-strength plugging belt, the compressive strength is only 7MPa, and carbonization occurs when the temperature is too high.

[0007] The first object of the present invention is to provide a composite plugging agent for drilling, comprising the following components in parts by weight: 30-40 parts of modified epoxy resin, 1-2 parts of diluent, 4-6 parts of curing agent and 10-14 parts of filler;

[0008] The modified epoxy resin is mainly made of the following raw materials in parts by weight: 20-30 parts of epoxy resin, 5-6 parts of N-ethylmorpholine and 4-6 parts of polyethylene glycol. The epoxy resin used is one or more of alicyclic epoxy resin, bisphenol A epoxy resin and amino epoxy resin.

[0009] The epoxy resin was modified by N-ethylmorpholine and polyethylene glycol, and the reaction equation is as follows:

[0010]

[0011] The epoxy resin provides basic bonding performance; N-ethylmorpholine can improve the temperature resistance of the epoxy resin; polyethylene glycol can improve the flexibility of the epoxy resin, thereby enhancing the compressive resistance of the composite plugging agent. The modified epoxy resin, diluent, curing agent and filler are used together to obtain a composite plugging agent with good solidification time and high temperature resistance (i.e., not easily carbonized).

[0012] As a possible design, the preparation method of the modified epoxy resin includes:

[0013] Grind the epoxy resin into powder, mix it with N-ethylmorpholine and react it at 110-120° C. for 30-40 minutes to obtain a mixed solution 1;

[0014] Add polyethylene glycol to the mixed solution 1, raise the temperature to 140-142°C, and react for 60-90 minutes.

[0015] The modified epoxy resin obtained by the method has good flexibility and temperature resistance.

[0016] As a possible design, the curing agent is mainly made of the following raw materials in parts by weight: 6-8 parts of m-nonylphenol, 4-6 parts of acetal resin, and 3-5 parts of m-xylenediamine. m-nonylphenol improves the flexibility of the curing agent, and m-xylenediamine improves the curing strength of the curing agent. The acetal resin used is one or more of PVB, PVA and POM.

[0017] This avoids the curing agent being too brittle and too flexible.

[0018] As a possible design, the preparation method of the curing agent includes:

[0019] Mix m-nonylphenol, acetal resin and one third to two thirds of m-xylylenediamine, and react at 80 to 90° C. for 80 to 90 minutes to obtain a mixed solution 2;

[0020] Add the remaining m-xylenediamine to the mixed solution 2, continue the reaction for 120-130 min, then raise the temperature to 140-150° C. and keep it for 50 min, and finally dehydrate.

[0021] As a possible design, the diluent is ethylene glycol diglycidyl ether or β-carboxyethyl acrylate.

[0022] As a possible design, the filler is a mixture of glass fiber, quartz sand and silicon dioxide.

[0023] As a possible design, the mass ratio of the glass fiber, quartz sand and silicon dioxide is 1:1:2-3.

[0024] The second object of the present invention is to provide a method for preparing a composite plugging agent for drilling, comprising:

[0025] The modified epoxy resin and the diluent are mixed and heated to 40 to 50 degrees Celsius, and then fillers are added thereto and mixed to obtain component A;

[0026] The curing agent is component B.

[0027] As a possible design, the diluent is added to the modified epoxy resin and stirred during the adding process, with a stirring speed of 120 to 130 r / min and a stirring time of 8 to 10 min.

[0028] The third object of the present invention is to provide a method for using a composite plugging agent for drilling, wherein component A and component B are mixed in a mass ratio of 1:1 to 6:1.

[0029] The beneficial effects of the present invention are as follows: the composite plugging agent for drilling prepared by the present invention not only has excellent high-strength performance, but also has good high-temperature resistance and suitable solidification time, and can achieve effective plugging, so it is worthy of popularization and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0031] Figure 1 It is a statistical diagram of critical temperature in performance detection in an embodiment of the present invention. DETAILED DESCRIPTION

[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0033] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.

[0034] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.

[0035] In the description of the present invention, it is necessary to understand that the directions or positional relationships indicated by the terms "up", "down", "front", "back", "left", "right", etc. are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0036] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0037] Example 1

[0038] The modified epoxy resin is prepared as follows:

[0039] S1. Take 20 parts of bisphenol A epoxy resin, crush it to 100 mesh, and then place it in a reaction kettle;

[0040] S2. Add 5 parts of N-ethylmorpholine into the reaction vessel, heat to 110°C, and react for 30 minutes;

[0041] S3. Add 5 parts of polyethylene glycol, heat to 140°C, react for 60 minutes, and obtain a modified epoxy resin after cooling.

[0042] Prepare the curing agent as follows:

[0043] S1. Add 6 parts of m-nonylphenol, 4 parts of acetal resin and 1 part of m-phenylenediamine into a reactor, then raise the temperature to 80°C and react for 80 minutes; the acetal resin is a mixture of PVB and PVA, which are mixed in a mass ratio of 1:1.

[0044] S2. Add 2 parts of m-phenylenediamine into the reactor, continue the reaction for 120 minutes, then raise the temperature to 150°C, keep the temperature for 50 minutes, and obtain the curing agent after dehydration.

[0045] Glass fiber, quartz sand and silicon dioxide are mixed in a mass ratio of 1:1:2 to obtain a filler. In this embodiment, 10 parts of the filler are used. The diluent is 1 part of ethylene glycol diglycidyl ether. In this embodiment, 30 parts of the modified epoxy resin are used, and 4 parts of the curing agent are used.

[0046] Preparation of drilling composite plugging agent, as follows:

[0047] Component A: Place the modified epoxy resin in a stirrer, add the diluent into the stirrer, stir and mix evenly, let it stand for 10 minutes, heat it to 50°C, add the filler, stir and mix evenly to obtain component A.

[0048] Among them, the speed of the stirrer is 120r / min and the stirring time is 8min.

[0049] Component B: curing agent.

[0050] The method of using the drilling composite plugging agent is: mix component A and component B in a mass ratio of 6:1, and then it can be used.

[0051] The basic performance results when components A and B are mixed in different proportions are shown in Table 1.

[0052] Table 1: Mixing performance record of components A and B in different proportions

[0053]

[0054]

[0055] As can be seen from Table 1, when the dosage of component A and component B is in different ranges, the state of the composite plugging agent is completely different. For example, when the dosage ratio of component A and component B is 8:1, the two will not solidify for a long time after mixing, while when the dosage of component A and component B is 1:2, the resulting composite plugging agent solidifies quickly but is brittle. Therefore, when the dosage range of component A and component B is 1:1 to 6:1, the two-hour compressive strength of the resulting composite plugging agent can reach 24Mpa, and the critical temperature can reach 280℃, with obvious compressive and high temperature resistance.

[0056] Example 2

[0057] The modified epoxy resin is prepared as follows:

[0058] S1. Take 25 parts of amino epoxy resin, crush it to 100 mesh, and then place it in a reaction kettle;

[0059] S2. Add 6 parts of N-ethylmorpholine into the reactor and heat to 115°C for 35 minutes;

[0060] S3. Add 5 parts of polyethylene glycol, heat to 141°C, react for 75 minutes, and obtain modified epoxy resin after cooling.

[0061] Prepare the curing agent as follows:

[0062] S1. Add 7 parts of m-nonylphenol, 5 parts of acetal resin and 1.3 parts of m-phenylenediamine into a reactor, then raise the temperature to 85°C and react for 85 minutes; the acetal resin is obtained by mixing PVB, PVA and POM, and the mass ratio of the three is 1:1:1.

[0063] S2. Add 2.7 parts of m-phenylenediamine into the reactor, continue the reaction for 125 minutes, then raise the temperature to 150°C, keep the temperature for 50 minutes, and obtain a curing agent after dehydration.

[0064] Glass fiber, quartz sand and silicon dioxide are mixed in a mass ratio of 1:1:2 to obtain a filler. In this embodiment, 12 parts of the filler are used. The diluent is ethylene glycol diglycidyl ether, a total of 2 parts. In this embodiment, 35 parts of the modified epoxy resin are used, and 5 parts of the curing agent are used.

[0065] Preparation of drilling composite plugging agent, as follows:

[0066] Component A: Place the modified epoxy resin in a stirrer, add the diluent into the stirrer, stir and mix evenly, let it stand for 10 minutes, heat it to 50°C, add the filler, stir and mix evenly to obtain component A.

[0067] Among them, the speed of the stirrer is 125r / min and the stirring time is 9min.

[0068] Component B: curing agent.

[0069] The method of using the drilling composite plugging agent is: mix component A and component B in a mass ratio of 6:1, and then it can be used.

[0070] Example 3

[0071] The modified epoxy resin is prepared as follows:

[0072] S1. Take 30 parts of amino epoxy resin, crush it to 100 mesh, and then place it in a reactor;

[0073] S2. Add 6 parts of N-ethylmorpholine into the reactor and heat to 120°C for 35 minutes;

[0074] S3. Add 6 parts of polyethylene glycol, heat to 142°C, react for 90 minutes, and obtain modified epoxy resin after cooling.

[0075] Prepare the curing agent as follows:

[0076] S1. Add 8 parts of m-nonylphenol, 6 parts of acetal resin and 1.7 parts of m-phenylenediamine into a reactor, then heat to 85°C and react for 85 minutes; the acetal resin is obtained by mixing PVB and POM, and the mass ratio of the three is 1:1.

[0077] S2. Add 3.3 parts of m-phenylenediamine into the reactor, continue the reaction for 130 minutes, then raise the temperature to 150°C, keep the temperature for 50 minutes, and obtain a curing agent after dehydration.

[0078] Glass fiber, quartz sand and silicon dioxide are mixed in a mass ratio of 1:1:2 to obtain a filler, and in this embodiment, 14 parts of the filler are used. The diluent is β-carboxyethyl acrylate, a total of 2 parts. In this embodiment, 40 parts of the modified epoxy resin are used, and 6 parts of the curing agent are used.

[0079] Preparation of drilling composite plugging agent, as follows:

[0080] Component A: Place the modified epoxy resin in a stirrer, add the diluent into the stirrer, stir and mix evenly, let it stand for 10 minutes, heat it to 50°C, add the filler, stir and mix evenly to obtain component A.

[0081] Among them, the speed of the stirrer is 125r / min and the stirring time is 9min.

[0082] Component B: curing agent.

[0083] The method of using the drilling composite plugging agent is: mix component A and component B in a mass ratio of 6:1, and then it can be used.

[0084] Comparison Example

[0085] Take 10 parts of propylene oxide propylene ether, 5 parts of hydroxyethyl acrylate, 30 parts of acrylic acid glycidyl, 15 parts of aminophenol and 40 parts of deionized water by mass, mix and react at 80°C for 4 hours to obtain an initial mixed solution; add sodium hydroxide solution accounting for 1.5% of the mass of the initial mixed solution after natural cooling, the mass concentration of the sodium hydroxide solution is 10%, mix and react at 50°C for 4 hours, wash with water and dry after natural cooling to obtain a high-strength temperature-resistant material; mix 25 parts of high-strength temperature-resistant material, 10 parts of sepiolite fiber, 5 parts of carbon fiber, 10 parts of river sand, 30 parts of limestone and 20 parts of mica flakes to obtain a composite plugging agent, and the prepared composite plugging agent has a particle size of 10 to 20 meshes.

[0086] Performance testing:

[0087] The methods of Example 1, Example 2 and Example 3 were used to prepare composite plugging agents, which were used as Experimental Group 1, Experimental Group 2 and Experimental Group 3, respectively, and the control example was used as the control group.

[0088] 1) The composite plugging agents prepared in each group were used for drilling plugging, and the compressive strength performance of each group was tested. The relevant data were recorded in Table 2.

[0089] The compressive strength test method is as follows: When the sample is under unconfined pressure and is compressed and damaged under longitudinal pressure, the load per unit area is called the compressive strength of the sample. That is, the ratio of the maximum load when the sample is damaged to the cross-sectional area perpendicular to the loading direction. The compressive strength test is suitable for all kinds of solid samples that can be made into regular specimens. Specific experimental steps: After the material is aged in the reactor for a certain period of time, a solid body is obtained, and the solid body is placed in the center of the pressure plate of the testing machine. The spherical seat is adjusted to make the two end faces of the specimen contact evenly, and the load is applied at a speed of 0.15 to 1.0 MPa per second until the specimen is damaged. The failure load and the phenomena that occur during the loading process are recorded. The experimental temperature is 100°C.

[0090] The experimental value of sample compressive strength is calculated according to the following formula:

[0091]

[0092] Where: Rc—test value of uniaxial compressive strength of rock, kPa; Pc—maximum load value when the sample is destroyed, kN; A—cross-sectional area of ​​the sample, m 2 .

[0093] Table 2: Record of compressive strength performance of each group

[0094]

[0095] It can be seen from Table 2 that compared with the control group, the compressive strength of the experimental groups (experimental group 1, experimental group 2 and experimental group 3) are better than that of the control group, and the difference between the experimental groups is not obvious. The high-strength drilling composite plugging agent provided by the present invention has excellent compressive strength performance.

[0096] The composite plugging agents prepared by each group were used for drilling plugging, and the temperature resistance of each group was tested. The relevant data are recorded in Table 3.

[0097] The method for determining the critical temperature is as follows: age the composite plugging agent in a reactor for 2 hours at different temperatures, take out the solid body and observe whether it can solidify and whether it is a compact solid. The critical temperature is the temperature at which the solid body cannot solidify, the final product is hollow or has a greatly reduced volume.

[0098] Table 3: Critical temperature records for each group

[0099] Group n Critical temperature(℃) Experimental Group 1 5 309 Experimental Group 2 5 315 Experimental Group 3 5 312 Control group 5 250

[0100] From Table 3 and Figure 1 It can be seen that compared with the control group, the temperature resistance of the experimental groups (experimental group 1, experimental group 2 and experimental group 3) is better than that of the control group, and the difference in temperature resistance between the experimental groups is not obvious. The high-strength drilling composite plugging agent provided by the present invention has good temperature resistance.

[0101] It should be noted that the above embodiments all belong to the same inventive concept, and the description of each embodiment has its own focus. For matters that are not described in detail in some embodiments, reference may be made to the description in other embodiments.

[0102] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A composite plugging agent for drilling, characterized in that: The invention comprises the following components in parts by weight: 30-40 parts of modified epoxy resin, 1-2 parts of diluent, 4-6 parts of curing agent and 10-14 parts of filler; The modified epoxy resin is mainly made of the following raw materials in parts by weight: 20-30 parts of epoxy resin, 5-6 parts of N-ethylmorpholine and 4-6 parts of polyethylene glycol.

2. The composite plugging agent for drilling according to claim 1, characterized in that: The preparation method of the modified epoxy resin comprises: Grind the epoxy resin into powder, mix it with N-ethylmorpholine and react it at 110-120° C. for 30-40 minutes to obtain a mixed solution 1; Add polyethylene glycol to the mixed solution 1, raise the temperature to 140-142°C, and react for 60-90 minutes.

3. The composite plugging agent for drilling according to claim 1, characterized in that: The curing agent is mainly made of the following raw materials in parts by weight: 6-8 parts of m-nonylphenol, 4-6 parts of acetal resin, and 3-5 parts of m-xylylenediamine.

4. The composite plugging agent for drilling according to claim 3, characterized in that: The preparation method of the curing agent comprises: Mix m-nonylphenol, acetal resin and one third to two thirds of m-xylylenediamine, and react at 80 to 90° C. for 80 to 90 minutes to obtain a mixed solution 2; Add the remaining m-xylenediamine to the mixed solution 2, continue the reaction for 120-130 min, then raise the temperature to 140-150° C. and keep it for 50 min, and finally dehydrate.

5. The composite plugging agent for drilling according to claim 1, characterized in that: The diluent is ethylene glycol diglycidyl ether or beta-carboxyethyl acrylate.

6. The composite plugging agent for drilling according to claim 1, characterized in that: The filler is a mixture of glass fiber, quartz sand and silicon dioxide.

7. The composite plugging agent for drilling according to claim 6, characterized in that: The mass ratio of the glass fiber, quartz sand and silicon dioxide is 1:1:2-3.

8. A method for preparing the composite plugging agent for drilling according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The modified epoxy resin and the diluent are mixed and heated to 40 to 50 degrees Celsius, and then fillers are added thereto and mixed to obtain component A; The curing agent is component B.

9. The preparation method according to claim 8, characterized in that: Add the diluent into the modified epoxy resin and stir it during the adding process. The stirring speed is 120-130 r / min and the stirring time is 8-10 min.

10. A method for using the composite plugging agent for drilling obtained by the preparation method according to claim 8 or 9, characterized in that: Mix component A and component B in a mass ratio of 1:1 to 6:1.

Citation Information

Patent Citations

  • High-strength drilling composite plugging agent and preparation method thereof

    CN112080262A

  • Polyurethane chemical grouting material and production method

    CN101220203A

  • Self-temperature-limited polyurethane grouting material and preparation method thereof

    CN102643531A

  • Modified polyurethane grouting material and preparation method thereof

    CN113817125A

  • Quick leak blocking glue for dangerous environment and its making method and use

    CN1616580A